An olefin metathesis approach towards the solomonamides. - Cheng-Sánchez, Iván; García-Ruiz, Cristina; Sarabia-García, Francisco Ramón (Elsevier, 2016)
A new synthetic strategy directed towards the solomonamides, a novel class of cyclopeptides of marine origin, has been developed utilizing an olefin metathesis reaction to form the [15]-membered ring contained in these natural products. We demonstrated the efficiency and validity of this synthetic approach for the construction of the macrocyclic core of the solomonamides in a minimally oxidized system. In fact, the olefin metathesis cyclization proceeded in a stereoselective manner to provide exclusively the Z-isomer in high yield. The described synthetic strategy for the solomonamides allows for access to the natural products, as well as offering the opportunity for the generation of a diverse set of analogues in the subsequent oxidation phase
Política de acceso abierto tomada de: https://v2.sherpa.ac.uk/id/publication/15870
Keywords: Química clínica; Solomonamides; Natural products; Ring-closing metathesis; Antiinflammatory agents; Diversity-oriented synthesis